Preserved Thermal Pain in 3xTg-AD Mice With Increased Sensory-Discriminative Pain Sensitivity in Females but Affective-Emotional Dimension in Males as Early Sex-Specific AD-Phenotype Biomarkers - Cañete, Toni; Giménez-Llort, Lydia (Frontiers in Aging Neuroscience, 2021)
The increase of the aging population, where quite chronic comorbid conditions are associated with pain, draws growing interest across its investigation and the underlying nociceptive mechanisms. Burn injuries associated problems might be of relevance in the older adult's daily life, but in people with dementia, exposure to high temperatures and heat sources poses a significantly increased risk of burns. In this brief report, the hind paws and tail pain withdrawal reflexes and the emotional responses to thermal nociception in 3xTg-AD mice were characterized for the first time in the plantar test and compared to their non-transgenic (NTg) counterparts. We studied a cohort of male and female 3xTg-AD mice at asymptomatic (2 months), early (6 months), middle (9 months) to advanced (12 and 15 months) stages of the disease and as compared to sex- and age-matched NTg control mice with normal aging. At 20 and 40W intensities, the sensorial-discriminative thresholds eliciting the withdrawal responses were preserved from asymptomatic to advanced stages of the disease compared to NTg counterparts. Moreover, 3xTg-AD females consistently showed a greater sensory-discriminative sensitivity already at premorbid ages, whereas increased emotionality was shown in males. False-negative results were found in ‘blind to sex and age’ analysis warning about the need to study sexes independently. The current results and previous report in cold thermal stimulation (Baeta-Corral et al., 2015) provide two paradigms unveiling sex-specific early AD-phenotype nociceptive biomarkers to study the mechanistic underpinnings of sex-, age- and AD-disease-dependent thermal pain sensitivity.